Comprehensive Scoping Review on Body Image Perceptions and Influences in Children and Adolescents - Suellem Zanlorenci; Leticia Gonçalves; Mikael Seabra Moraes; Leandro Narciso Santiago; Matheus Silveira Pedroso; Diego Augusto Santos Silva (MDPI AG, 2024)
Conducting a scoping review helps identify research gaps and opportunities, avoid duplication, guide the selection of appropriate methodologies, and base studies on existing evidence. The aim of this study was to map the literature on body image in children and adolescents (0 to 19 years). The present study follows the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA). The search was conducted in the following databases: PubMed, Web of Science, Scopus, SPORTDiscus, LILACS, SciELO, PsycINFO, CINAHL, and the Cochrane Library. A total of 3257 articles were found, of which 2147 were duplicates, resulting in 1110 articles. Of these, 41 met the inclusion criteria. The results were divided into analytical dimensions, including measurement instruments, programs and interventions, social media, sociodemographic aspects, physical activity, personality and cognitive thinking, and studies with specific populations. The results highlight that peer influence, physical activity, media, and the school environment play crucial roles in shaping young people's body image; factors such as sex, age, and socioeconomic context emerge as important variables in understanding body perceptions, and educational interventions and health promotion programs have been shown to be effective in preventing and reducing body dissatisfaction, underscoring the need for multifactorial and collaborative approaches.